External Validation of ASPECT (Algorithm for Suspected Pulmonary Embolism Confirmation and Treatment). Issue 8 (August 2019) - Klil-Drori, Adi J.; Prajapati, Dwip; Liang, Zhiying; Wang, Meng; Toupin, Dominique; Alothman, Latifah; Lang, Eddy; Suryanarayan, Deepa; Tagalakis, Vicky
Abstract : Background: Administrative health care databases are increasingly being used to study pulmonary embolism (PE), but the validity of single PE codes is variable. Using data from Quebec, Canada, we developed ASPECT (Algorithm for Suspected Pulmonary Embolism Confirmation and Treatment), combining 3 components to ascertain confirmed PE: emergency department (ED) diagnoses, imaging codes, and dispensed prescriptions or hospital diagnoses. Herein, we used unrelated administrative health care databases to externally validate ASPECT. Methods: We used ED electronic health records (ED-EHRs) to identify all residents of Calgary (Alberta, Canada) with PE codes between January and June, 2016. We applied ASPECT by identifying imaging studies in the ED-EHR, admission diagnoses in linked discharge abstract database and filled prescriptions in linked pharmacy information. Confirmed PE in ASPECT was validated against chart review in the ED-EHR. Results: The cohort included 498 patients. Overall, 258 (51.9%) were managed as outpatients and 327 were adjudicated to have confirmed PE; the positive predictive value (PV) of single PE codes was 65.6%. With ASPECT the positive PV was 96.5% [95% confidence interval (CI), 94.4–98.5%] and positive likelihood ratio was 10.9 (95% CI, 6.8–15.1). The negative PV and negative likelihood ratio were 85.1% (95% CI, 80.0–90.2%) and 0.1 (95% CI, 0.0–0.1), respectively. Overall agreement of ASPECT with confirmed PE was 92.2%. Further, ASPECT was similarly robust in inpatients and outpatients and was more precise than any 2-component combination of ASPECT. Conclusions: Our findings reiterate the limitations of using single administrative codes for PE and suggest ASPECT as an acceptable tool to study PE.